Asymmetric information, credential assessment services and earnings of new immigrants - Stein Monteiro (Journal of Applied Economics, 2022)
Based on the 2016 Canadian Census of Population, some immigrant groups have higher entry-earning returns on their ability than others, and experience a lot more variation in earnings given similar variations in ability compared to other groups. The uneven variance in earnings given similar variances in ability is an indication of statistically discriminated immigrant groups due to information gaps. I show that credential assessment is an essential service to reduce information gaps between employers and immigrant workers. While assessors do not reveal an immigrant worker's true ability without error, they may supply contextual and/or specific information about the worker and their source country. The more about the source country that goes unexplained, variance in ability and immigration increases, while variance in earnings decreases. However, these results are generated only if the credential assessor faces considerable difficulty in learning about the source country and migrants are of low ability.
Keywords: 330; asymmetric information; credential assessment services; entry earnings; immigrants; labour market intermediaries; Statistical discrimination; unobserved ability